A Call to Action: An IWG Charter for a Public Health Approach to Dying, Death, and Loss. (December 2014) - Becker, Carl; Clark, Elizabeth; Despelder, Lynne A.; Dawes, John; Ellershaw, John; Howarth, Glennys; Kellehear, Allan; Kumar, Suresh; Monroe, Barbara; O'Connor, Patrice; Oliviere, David; Relf, Marilyn; et al.
The current systems of care for dying persons, the people caring for them, and the bereaved operate in ways that frequently lack sufficient sensitivity to their needs. We describe a new model for dying, death, and loss that adopts a public health approach. Specifically, we describe a deliberative process that resulted in a charter for a public health approach to dying, death, and loss. Modeled after the World Health Organization's 1986 Ottawa Charter, our charter includes a call to action. It has the potential to bring about significant change on local, societal, and global levels as exemplified by four projects from three countries. Public health and end-of-life services and organizations need to form partnerships with the community to develop a public health approach to dying, death, and loss. Learning from each other, they will affirm and enhance community beliefs and practices that make death part of life.